MIGRASI, PEREBUTAN AKSES TANAH DAN PENGUATAN LEMBAGA ADAT: RESOLUSI KONFLIK TANAH DI RANTAU MINANGKABAU - Undri, Undri (Jurnal Masyarakat dan Budaya, 2009)
This writing wants to describe about how three ethnic groups, Minangkabau, Mandailing and Java are scrambling the land in area of Pasaman. In the area of Minangkabau rantau, Minangkabau ethnics as aborigine assumed two ethnic that are Mandailing and of Java have grab their property of the land existed in their area. Early from massive refuge of Mandailing’s people in 1930. Have been noted from 37.612 one who have migration to all Indonesia region counted 25.945 people (68.9%) have migration to area of West Sumatra, especially to Pasaman. Because the native land of Mandailing located near north side Pasaman. In struggling of land conflict which refers to the form of violent cannot be avoided. The Phenomenon like this make them to be ”hungry faction” (land hunter). According to Langenberg’s work in comprehending the typology of Mandailing people in acquiring the land. The conflict was more massive, when in 1950th era the central government delivers Java ethnic come to native land of West Sumatra under transmigration policy. The attendance of them on the land often triggers the local resident conflict particularly concerning the property of the land. Because local resident still assume that the land have been occupied by transmigrant from Java still under their property. Although by local head village have delivered the land to new comer. In solving the conflict mentioned above the role of customary institute play the important role by placing forward the deliberation. The rounded water under vessel and one word under general consensus. The aphorism mentioned above identifes us that all kinds of existing problem in Minangkabau can be finished by deliberation. In fact, the conflict that happened is only finished by informal institute namely by involving elite figure to look for the feasible solution of that. Keyword: Land conflict, migration, access struggle of the land, reinforcement of customary institute, conflict resolution, outside of native land of Minangkabau.